Gas Reform in Ukraine : Monopolies, Markets, and Corruption - Lovei, Laszlo (World Bank, Washington, DC, 2012)
Reform of the natural gas industry in Ukraine started a year later than reform of the power industry. Because gas reform had no blueprint, its direction has remained ambiguous. That ambiguity is the result of a conflict between those who advocate vertically integrated, opaque, monopolistic structures and those who want a transparent, competitive gas market governed by stable rules. This conflict will likely continue for several years, making the ultimate outcome difficult to predict. More by accident than by design, the reform produced a number of innovative features that might be of interest for other countries planning to restructure and privatize their gas industries.